The Effectiveness Of Islamic Law Implementation To Address Cyber Crime: Studies In Arab, Brunei Darussalam, And China - Uswatun Hasanah (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2018)
Technology development cause crime in the world that keep fluctuating and changing. Cyber crime is one of crime activities which takes place in the internet and develop fast globally, even faster than the conventional crime. Cyber crime is not only about computer-crime, cyber-terrrorist, cyber-narco-terrorist, but also capable to make impact toward state economy. This paper aims to understand the implementation of Islamic law or Islamic criminal law to see cyber crime. Islamic criminal law has been developed many years ago before arrival of information technology. This paper describes how Arab, Brunei Darussalam, and China reduce crime by adoption of islamic law. Islamic law what meant here is a law based on Islam, not a law made by Muslims then applied by Muslims. Islamic law can be practiced in every single country, although they don't declare explicitly or they think that what have they done is not islamic law. Islamic law contains general principles to respon and develop efficient ways to overcome cyber-crime.